ADMINISTRATIVE & GENERAL COSTS ON NET PROFIT - Asep Mulyana; Endang Susilawati (Universitas Widyatama, 2021)
This study aims to determine the effect of general & administrative costs on net income. The method used in this research is descriptive statistical method. The type of research used is quantitative. The results of the study show that the cost of raw materials partially has a significant effect on net income